A redox-responsive dihydroartemisinin dimeric nanoprodrug for enhanced antitumor activity - Yawei Li; Qing Pei; Baiji Cui; Hongmei Zhang; Liu Han; Wenqing Li; Wenhe Zhu; Xianmin Feng; Zhigang Xie (Journal of Nanobiotechnology, 2021)
Abstract Redox-responsive drug delivery system emerges as a hopeful platform for tumor treatment. Dihydroartemisinin (DHA) has been investigated as an innovative tumor therapeutic agent. Herein, a DHA dimeric prodrug bridged with disulfide bond as linker (DHA2-SS) has been designed and synthesized. The prepared prodrugs could self-assemble into nanoparticles (SS NPs) with high DHA content (> 90%) and robust stability. These SS NPs display sensitive redox responsive capability and can release DHA under the tumor heterogeneity microenvironment. SS NPs possess preferable antitumor therapeutic activity in contrast with free DHA. Moreover, the possible anti-cancer mechanism of SS NPs was investigated through RNA-seq analysis, bioinformatics and molecular biological method. SS NPs could induce apoptosis via mitochondrial apoptosis pathway, as well as glycolysis inhibition associate with the regulation of PI3K/AKT/HIF-1α signal path, which may offer an underlying therapeutic target for liver cancer. Our study highlights the potential of using redox responsive prodrug nanoparticles to treat cancer, meanwhile provides insights into the anti-cancer mechanism of DHA prodrug. Graphical Abstract